Możliwości rozwoju ubezpieczeń ekologicznych w Polsce na tle niemieckiego rynku ubezpieczeń ekologicznych - Panasiewicz, Agnieszka (Possibilities of the Environmental Insurance Development in Poland on the Backround of German Environmental Insurance, 2005)
The business is still developing and also the aspiration of people to aim more and more benefits give the occasion to set a number of the new impendences - particularly those unknown till now. They can cause different damages not only in field of the people activity but also in the personal and financial area.That is why the new instruments are implemented in all the environment area worldwide. Among those instruments the most popular is the environmental insurance. This kind of insurance function in a number of countries, in Poland we can say about the first phase of development. The implementation of this kind of insurance in Poland in the wide-spread scale is inevitable, so Poland can use the experience of the other countries, which implemented the environmental insurance much more earlier - e.g. Germany.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 100-108